Comparison of Fluconazole with Oral Probiotic and Fluconazole in the Treatment of Vulvovaginal Candidiasis : A Systematic Review And Meta-Analysis Of RCT Studies - Intan Purnama; Susilawati Susilawati; Gita Dwi Prasasty (Program Studi Pendidikan Biologi, 2025)
Vulvovaginal candidiasis, a common fungal infection that affects up to 75% of women at least once in their lifetime. With increasing resistance to azole antifungals, such as fluconazole, due to factors such as gene efflux pumps, alternative treatments are needed. Probiotics, specifically Lactobacillus species, have emerged as a promising option due to their ability to inhibit Candida albicans and modulate the host immune response. This study analyzed data from randomized controlled trials. We collected data from articles comparing probiotics with fluconazole therapy and fluconazole alone with or without placebo in patients with vulvovaginal candidiasis published between 2009 and 2024. We obtained articles from scientific databases such as Scopus, Pubmed, ScienceDirect, Clinical Key, JSTOR and Google Scholar based on inclusion criteria. Data analysis was performed using Review Manager Version 5.4.1. The results showed that probiotics significantly reduced symptoms of vaginal discharge (OR value = 0.14 (0.07,0.29), 95% CI) and improved culture test results (OR value = 0.33 (0.17,0.63), 95% CI), indicating potential benefits in improving vaginal microbiota balance and preventing recurrent infections. However, probiotics did not significantly relieve other symptoms, such as itching (OR value = 0.67 (0.27,1.61), 95% CI), irritation (OR value = 0.56 (0.25,1.24), 95% CI), and dyspareunia (OR value = 0.91 (0.34,2.43), 95% CI). For individuals with vulvar candidiasis who are unresponsive to fluconazole therapy, probiotic drugs can be given as additional therapy